2022
DOI: 10.1177/20451253221117313
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology, prognosis and treatment of tardive dyskinesia

Abstract: Tardive dyskinesia (TD), a movement disorder associated with antipsychotics, most frequently affects the lower face and jaw muscles, but can also affect walking, breathing and use of the hands and limbs. Knowledge of TD among physicians may be limited, and the pathophysiology of TD is poorly understood. We conducted this review to summarise the current knowledge surrounding the pathophysiology of TD and present recommendations for prevention and treatment based on a literature search and roundtable discussion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 138 publications
0
12
0
Order By: Relevance
“…1 All patients on antipsychotics require frequent metabolic and movement disorder monitoring to ensure proper disease and adverse drug reaction management, regardless of age, race, diagnosis, antipsychotic used, or dose. 2,3 Proper monitoring can increase the quality of life, ensure proper disease management, and decrease morbidity and mortality. According to the American Psychiatric Association (APA) Practice Guidelines for the Treatment of Patients with Schizophrenia and use of antipsychotics, 4 monitoring parameters should include glucose, hemoglobin A1C (Hgb A1C), lipids, weight, body mass index (BMI), waist circumference, and movement disorder testing for extrapyramidal syndromes (EPS).…”
Section: Background 1| Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 All patients on antipsychotics require frequent metabolic and movement disorder monitoring to ensure proper disease and adverse drug reaction management, regardless of age, race, diagnosis, antipsychotic used, or dose. 2,3 Proper monitoring can increase the quality of life, ensure proper disease management, and decrease morbidity and mortality. According to the American Psychiatric Association (APA) Practice Guidelines for the Treatment of Patients with Schizophrenia and use of antipsychotics, 4 monitoring parameters should include glucose, hemoglobin A1C (Hgb A1C), lipids, weight, body mass index (BMI), waist circumference, and movement disorder testing for extrapyramidal syndromes (EPS).…”
Section: Background 1| Introductionmentioning
confidence: 99%
“…In the United States alone, over 4 million adults are currently on antipsychotic medications 1 . All patients on antipsychotics require frequent metabolic and movement disorder monitoring to ensure proper disease and adverse drug reaction management, regardless of age, race, diagnosis, antipsychotic used, or dose 2,3 . Proper monitoring can increase the quality of life, ensure proper disease management, and decrease morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…
227Tardive dyskinesia(TD) is a movement disorder that exhibits a range of clinical manifestations arising as side effects of treatment with dopamine receptor-blocking agents, primarily antipsychotic drugs (APDs) [1,2].Consequently,its management overlaps different disciplines, in particular, psychiatry and neurology.In practice, this canresult ina gap in management whereby patients receive only one aspect of what should ideally bemultidisciplinarycare. Psychiatrists will naturally focus on controllingthe patient'schallenging psychotic symptomsand may not be specialized in the evaluation of the abnormal movements that are a core manifestation of TD [3,4].As a result, exposure of neurologists to TD patients may be limited to when the condition has becomesevere.
…”
mentioning
confidence: 99%
“…Therefore, it is currently unclear whether these abnormalities are non-specific factors common to many disorders or whether they have a specific pathogenetic role. The influence of treatments is also unclear, although treatments are usually considered useful in reducing oxidative stress (Lepping et al , 2011; Dietrich-Muszalska et al , 2021; Mariani et al , 2022), the opposite has also been reported, at least in some body tissues (Kropp et al , 2005; Dietrich-Muszalska and Kolińska-Łukaszuk, 2018; Todorović Vukotić et al , 2021). The paper by Yazla (Yazla et al , 2023) in this issue reports an interesting analysis of oxidative stress parameters and serum prolidase enzymatic activity, an enzyme usually associated with oxidative stress.…”
mentioning
confidence: 99%
“…Tardive dyskinesia is now less of a concern due to the reduced risk posed by newer antipsychotics, but it is still present and therefore treatments are needed. Besides clozapine, there is some evidence for other treatments such as deutetrabenazine, pyridoxine, melatonin and repetitive transcranial magnetic stimulation (Taylor et al, 2021;Takeuchi et al, 2022). The recently approved valbenazine, with its innovative mechanism of action, is a significant improvement.…”
mentioning
confidence: 99%